2022
DOI: 10.1186/s12915-022-01358-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional regeneration of the murine neuromuscular synapse relies on long-lasting morphological adaptations

Abstract: Background In a broad variety of species, muscle contraction is controlled at the neuromuscular junction (NMJ), the peripheral synapse composed of a motor nerve terminal, a muscle specialization, and non-myelinating terminal Schwann cells. While peripheral nerve damage leads to successful NMJ reinnervation in animal models, muscle fiber reinnervation in human patients is largely inefficient. Interestingly, some hallmarks of NMJ denervation and early reinnervation in murine species, such as frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…This was achieved by assessing the coincidence of presynaptic motor neuron staining with antibodies to NF and SV2 and postsynaptic AChR marked by BTX in the injured legs compared with uninjured contralateral legs 14 dpi. In accordance with previous studies ( 42 , 43 ), partial recovery of innervation was observed in vehicle-treated controls at 14 dpi. Pharmacological inhibition of 15-PGDH increased innervation in injured EDL muscles from 84.5 ± 2.2% in vehicle-treated controls to 97.4 ± 2.1% in PGDHi-treated mice (Fig.…”
Section: Resultssupporting
confidence: 92%
“…This was achieved by assessing the coincidence of presynaptic motor neuron staining with antibodies to NF and SV2 and postsynaptic AChR marked by BTX in the injured legs compared with uninjured contralateral legs 14 dpi. In accordance with previous studies ( 42 , 43 ), partial recovery of innervation was observed in vehicle-treated controls at 14 dpi. Pharmacological inhibition of 15-PGDH increased innervation in injured EDL muscles from 84.5 ± 2.2% in vehicle-treated controls to 97.4 ± 2.1% in PGDHi-treated mice (Fig.…”
Section: Resultssupporting
confidence: 92%
“…These findings hold substantial importance in understanding motor deficits associated with DCM. Notably, our model deviates from traditional neuromuscular models characterized by partial or complete denervation, axonal swelling, and significant alterations in NMJ structure ( Valdez et al, 2010 ; Torres-Benito et al, 2011 ; Bermedo-García et al, 2022 ). Partially, these disparities might arise from a more direct mechanism in which motoneurons and their corresponding target myofibers are concurrently lost, leaving the tissue with limited capacity to compensate for the damage.…”
Section: Discussionmentioning
confidence: 83%
“…This peripheral cholinergic synapse is constituted by an extra-laminar capping of kranocyte cells, a presynaptic motor nerve terminal, a postsynaptic muscle specialization evidenced by clusters of acetylcholine receptors (AChRs), and non-myelinated terminal Schwann cells (tSCs; Sanes and Lichtman, 2001 ; Wu et al, 2010 ; Shi et al, 2012 ; Tintignac et al, 2015 ). Multiple pathologies, nerve or muscular injuries, lack of physical activity, and aging impair the synaptic structure and function at the NMJ, resulting in poly-innervation, partial or total denervation, postsynaptic fragmentation, and muscle atrophy, among other phenotypes ( Valdez et al, 2010 , 2012 ; Tejero et al, 2016 , 2020 ; Woehlbier et al, 2016 ; Bermedo-García et al, 2022 ). However, the behavior of the cellular components of the neuromuscular synapse in the context of DCM has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we did not study the functional regeneration of muscle fibers after an acute injury in the control and macrophage-depleted groups. The contraction of muscle fibers could be explored by high-speed imaging of second harmony generation (SHG) 91 and the functional repair of the neuromuscular junctions (a synaptic connection between terminal end of a motor nerve and a muscle) 92,93 could also be studied further.…”
Section: Discussionmentioning
confidence: 99%